2012
DOI: 10.1212/wnl.0b013e3182704056
|View full text |Cite
|
Sign up to set email alerts
|

Injury markers predict time to dementia in subjects with MCI and amyloid pathology

Abstract: In subjects with MCI and evidence of amyloid pathology, the injury markers CSF t-tau and p-tau and hippocampal atrophy can predict further cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(87 citation statements)
references
References 30 publications
10
71
3
3
Order By: Relevance
“…Considering the age-dependent tau accumulation found in HC in the present study, tau may have a primary triggering effect. When gradually accumulated tau exceeds a certain threshold, pathological Aβ accumulation may start inducing rapid AD progress (tau first, amyloid second theory) [4,5,14].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the age-dependent tau accumulation found in HC in the present study, tau may have a primary triggering effect. When gradually accumulated tau exceeds a certain threshold, pathological Aβ accumulation may start inducing rapid AD progress (tau first, amyloid second theory) [4,5,14].…”
Section: Discussionmentioning
confidence: 99%
“…These data support the hypothesis that modified Ab metabolism precedes tau-related disease and neuronal degeneration. The other study has disclosed that MCI subjects with elevated concentrations of injury markersnamely, t-tau and p-tau -may develop faster, therefore presenting shorter time to conversion [101]. Since both analyses are crosssectional in regards to the biomarker data, the use of multiple longitudinal CSF specimens is necessary to detect the time point at which CSF biomarkers convert from physiologic to pathologic values.…”
Section: Time Course Of Ad Biomarkersmentioning
confidence: 99%
“…After an average follow-up of 9 years, approximately 90% of the subjects with a combination of abnormal Ab1-42 and tau in CSF converted to AD-type dementia [4]. We found that 30% of the subjects with abnormal CSF Ab1-42 and normal injury markers converted to AD-type dementia after 4 years compared with 80-90% of the subjects with abnormal CSF Ab1-42 and one or more abnormal injury markers [15].…”
Section: Interpretation Of Ad Biomarker Scoresmentioning
confidence: 63%